The Comparison of Phonological Perceptions between Extrovert and Introvert Deaf Students - Rachman, Achmad Fajar; Yulianto, Bambang; Suhartono, Suhartono (International Journal for Educational and Vocational Studies, 2020)
The aim of this study is to identify the comparison of phonological perceptions by extroverted and introverted deaf students. This research is a type of qualitative research. The data of this study focuses on phonological perceptions which are realized in the form of deaf students' writing which is based on the utterances of researcher. Deaf students wrote down all the words given by the researcher based on their knowledge and understanding. The data sources were from the tenth grade students of SMALB B Karya Mulia, which totaling 10 students. Data collection techniques used are the assignment. The data analysis technique used is the basic technique of determining the determinant elements (PUP) and advanced techniques in the form of an equalizing relationship technique (HBS). The PUP technique is used to sort out the contexts that come from deaf students by using orthographic power that is adjusted to the determining instrument, namely writing. The findings of this study can be mentioned as follows: There are two findings in this study, namely (1) The quality of the perspectives of extroverted deaf students over introverts, and (2) Variations in perceptions of extroverted deaf students under introverts.